(untitled) (Diametros, 2015)
Hume’s view that the object of moral feeling is a natural passion, motivating action, causes problems for justice. There is apparently no appropriate natural motive, whilst, if there were, its “partiality” would unfit it to ground the requisite impartial approval. We offer a critique of such solutions as that the missing non-moral motive is enlightened self-interest (Baier), or that it is feigned (Haakonssen), or that it consists in a just disposition (Gauthier). We reject Cohon’s postulation of a moral motive for just acts, and also Harris’s attempt to dispense with motive as the source of their merit, by invoking extensive sympathy, and citing their beneficial societal consequences. These solutions assume that, if Hume remains a virtue ethicist, the natural virtues supply the paradigm. Taylor claims that a revolution in motivational psychology follows the inauguration of the artificial convention of justice, remoulding the natural virtues. This solution founders, we argue, upon unresolved contradictions besetting even these virtues